Islamic Views on The Law of Playing in Timezone that Contain the Gharar System - Izzuddin, Muhammad Fatih; Shauqi, Muhammad; Amalia, Nurul (ALFATWA jurnal tentang hukum dan syariat, 2025)
This research reviews the perspective of Islamic law regarding the activity of playing at Timezone, especially those that involve elements of gharar (uncertainty) and speculation. The game system in these places often uses a coin or balance exchange mechanism to access various games with unpredictable results, as well as elements of luck. Based on fiqh muamalah, the elements of gharar and maysir (gambling) are not allowed because they have the potential to create losses for one party and violate the principle of fairness in transactions. This research uses a qualitative method with a literature study approach to evaluate the legal validity of these games in Islam. Based on the research findings, the majority of games in Timezone with elements of uncertainty of outcome and speculation are categorised as haram because they involve gharar and maysir. However, games that rely entirely on skill and do not contain speculation, can be declared permissible or allowed. Therefore, Muslims should understand the characteristics of such games in order to avoid activities that are against Islamic law.